Development of a web-based computer specification advisory system using knowledge base approach / Hardie Yusof - Yusof, Hardie (2006)
Nowadays, web-based is important in business environment. It gives lots of services directly to customers and faster information. For a faster and accurate decision, people try to use advisory system in every field. With an existence of a web-based computer advisory system, it helps the user to see a recommendation for a specific computer components needed to build a computer. The recommendation is based on the budget value keyed in by the user. Services like catalogs and ordering are only made for someone who had knowledge about the technology. What about the user who does not obtain the knowledge or in a different field of work and expertise. People always find a problem in buying the right things based on what that they really need and their poor decision will lead to a waste of time and money. To produce a better recommendation the advisory system need a very large scale of data, thus sources from expertise needed to collect and restrain enough information. Implementation of knowledge base is where all the data is collected from different computer expertise. The system used data manipulation technique and backward chaining technique, where all data are gathered and stored using data manipulation technique. To find resuh for recommendation, the backward chaining is used where all the data is gathered and analyzed whether it can be used together and brings to a final product. All the hardware that matches then will be analyzed again to match budget given and the optional requirement. As a result a proper hardware will be selected to fulfill all the specification for building a personal computer. It is helpful and easier if there is an advisory system in the computer technologies field that can gives advantages for all kind of user who is on different field. Such development will totally improve people decision making and kept all the expertise knowledge.